Analysis of Students' Scientific Literacy Abilities on Environmental Changes Concepts - Lestari, Iing Dwi; Usman, Usman; Maulida, Siti Solihah; Fasyyaha, Zihma; Susanti, Laela Amalia; Yasir, Ghaliyah; Asyah, Ratu Qori (Universitas Sultan Ageng Tirtayasa, 2024)
This research aimed to describe the profile of students' scientific literacy abilities on environmental change. The sample in this research was class X students at a senior high school in Pandeglang, Indonesia. This research uses a descriptive method; data collected using scientific literacy skills tests and interviews. The research results show that students' average scientific literacy ability is 46.61%. Students' ability to explain scientific phenomena is 43%, evaluate and design scientific investigations is 56%, interpret scientific evidence and data is 37%, interest in scientific issues is 48%, support for inquiry activities is 52%, and response to natural resources and the environment by 78%. Based on the results of the interviews, that the learning process in schools still needs to develop students' scientific literacy skills.